2015
DOI: 10.1007/s11277-015-2785-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of an Intelligent Mobile Assistant Medical (IMAM) of the Heterogeneous Data for the Telemedicine Services: Design and Implementation

Abstract: The development of adaptable mobile applications on heterogeneous environments is still a complex problem today. These conceived applications must be able to be carried out and adapted according to their use context. The analysis of this dynamic adaptation required to study the parameters of the mobile environment in order to optimize the performances and to better exploit the environment conditions. We propose within the framework of this article, the design and implementation of a tool for generation of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Laparoscopic surgery has small trauma, quicker recovery of intestinal function, less intraoperative complications, light postoperative pain, small body's immune disturbance, the advantages of rapid recovery, shorter hospitalization time, laparoscopic amplification effect at the same time, and clear field of vision and will not damage the surrounding tissue organs. Laparoscopic surgery has the advantages of low incidence of incisional hernia and beautiful incision [ 8 , 9 ]. In recent years, laparoscopy is a minimally invasive technique, has been widely used in the operation in all the subjects, and has achieved very considerable success; gastrointestinal surgery is of no exception to the direction of minimally invasive, and studies have shown that laparoscopic surgery in the treatment of gastrointestinal surgery showed good effect, but, because of the large trauma of gastrointestinal tumors with carbon dioxide pneumoperitoneum, operation, and anesthesia, postoperative gastrointestinal dysfunction is seen, with even intestinal obstruction and other serious complications, so to promote the recovery of gastrointestinal function, reducing the incidence rate of complications is the key to improve the curative effect of patients.…”
Section: Application Of Intelligent Medical Monitoring Device In the Nursing Of Rectal Cancer Patients After Laparoscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic surgery has small trauma, quicker recovery of intestinal function, less intraoperative complications, light postoperative pain, small body's immune disturbance, the advantages of rapid recovery, shorter hospitalization time, laparoscopic amplification effect at the same time, and clear field of vision and will not damage the surrounding tissue organs. Laparoscopic surgery has the advantages of low incidence of incisional hernia and beautiful incision [ 8 , 9 ]. In recent years, laparoscopy is a minimally invasive technique, has been widely used in the operation in all the subjects, and has achieved very considerable success; gastrointestinal surgery is of no exception to the direction of minimally invasive, and studies have shown that laparoscopic surgery in the treatment of gastrointestinal surgery showed good effect, but, because of the large trauma of gastrointestinal tumors with carbon dioxide pneumoperitoneum, operation, and anesthesia, postoperative gastrointestinal dysfunction is seen, with even intestinal obstruction and other serious complications, so to promote the recovery of gastrointestinal function, reducing the incidence rate of complications is the key to improve the curative effect of patients.…”
Section: Application Of Intelligent Medical Monitoring Device In the Nursing Of Rectal Cancer Patients After Laparoscopic Surgerymentioning
confidence: 99%
“…Monitoring Device in the Nursing of Rectal Cancer Patients after Laparoscopic Surgery [8,9]. In recent years, laparoscopy is a minimally invasive technique, has been widely used in the operation in all the subjects, and has achieved very considerable success; gastrointestinal surgery is of no exception to the direction of minimally invasive, and studies have shown that laparoscopic surgery in the treatment of gastrointestinal surgery showed good effect, but, because of the large trauma of gastrointestinal tumors with carbon dioxide pneumoperitoneum, operation, and anesthesia, postoperative gastrointestinal dysfunction is seen, with even intestinal obstruction and other serious complications, so to promote the recovery of gastrointestinal function, reducing the incidence rate of complications is the key to improve the curative effect of patients.…”
Section: Application Of Intelligent Medicalmentioning
confidence: 99%
“…An electrical representation of contractile activity is used for the short-term assessment of cardiovascular diseases, especially for people with chronic heart problems. [23,201,215,216].…”
Section: Concern For Prioritisation Processmentioning
confidence: 99%
“…Measure the physiological data of the systolic and diastolic blood pressure of the patient. [23,201,216].…”
Section: Bpmentioning
confidence: 99%